HUBUNGAN ORIENTASI, PARTISIPASI POLITIK TERHADAP PERILAKU PEMILIH DALAM PILKADA WALIKOTA KUPANG 2017 - Juliansyah, Andry (Sapientia Humana: Jurnal Sosial Humaniora, 2021)
This research looks at the relationship between independent and dependent variables, with the formulation of the problem is: (1) the relationship of Political Orientation to Voter Behavior (2) the relationship of Political Participation to Voter Behavior (3) the relationship of Political Orientation to Voter Political Participation (4) the relationship of Political Orientation and Political Participation to Voter Behavior. The approach used in this study is a quantitative approach, while the data collection techniques used were, questionnaire and documentation study. Result of the study (1) Variable X1 to variable Y r value 0,237 is a positive relationship,